Factors Influencing the Consumption Behavior of Instant Noodles Among Undergraduate Students in the Public Health Program at STIKES Eka Harap Palangka Raya - Teguh Setiawan; Eva Prilelli Baringbing; Merry Delyka (PROMOTOR, 2026)
Background: Instant noodle consumption among students is increasing due to factors such as convenience, affordability, and wide availability. However, excessive consumption can have negative health effects, such as hypertension and metabolic risks. Indonesia ranks second in the world in terms of instant noodle consumption, with 14.540 billion servings. Research Objective: To analyze the factors influencing instant noodle consumption behavior among students in the Public Health Program at STIKES Eka Harap Palangka Raya. Method: This study used a quantitative approach with an analytical design. The sample in this study consisted of the entire population of students in the study program, totaling 79 people, using total sampling technique. Data were collected through questionnaires regarding respondent characteristics, knowledge, peer influence, duration of social media use, pocket money, and availability of instant noodles. Results: The study shows that knowledge (p-value = 0.01 < 0.05) and peer influence (p- value = 0.02 < 0.05) have a significant relationship with instant noodle consumption behavior. Meanwhile, duration of social media use, pocket money, and availability of instant noodles (P-value > 0.05) did not show a significant relationship. Conclusion: Two variables were found to have a significant influence, namely the factor of knowledge on instant noodle consumption behavior among students, and the influence of peers on instant noodle consumption behavior. Students are expected to be more discerning in choosing the food they consume on a daily basis.